The Effect of Digital Leadership, organizational culture, digital competence and organization's commitment on Organizational Performance: Information Technology System in Indonesian Navy - T, Puliwarna; Djati, S. Pantja; Tanti P., Elisabeth (International Journal of Scientific Research and Management (IJSRM), 2023)
The phenomenon of organizational performance within the TNI AL Headquarters has not been optimally assisted by the existence of existing information technology. The work process becomes less responsive because a lot is done manually. The purpose of this study is to explain the influence of digital leadership, digital competence and digital culture of crew members to improve the performance of the Indonesian Navy's organizations. The research sample was taken by purposive and cluster random sampling by selecting respondents who became operators or were involved in the use of information systems in their work units. The total sample of 445 respondents was obtained from 11 Navy's organizations of the Indonesian Navy Headquarters, which in total had a crew of 1,400 people, but the population involved in IT operations was approximately 800 people. The results of this study indicate that digital leadership has a direct positive and insignificant effect on organizational performance, The direct effect is shown in the positive and insignificant direct influence of digital leadership on organizational performance; while the direct effect is positive and significant digital competence, and organizational commitment to organizational performance; negatively and significantly direct effect of digital culture on organizational performance within the Indonesian Navy Headquarters. Digital competence directly has a positive and significant effect on organizational performance as well as on organizational commitment. Digital culture has a direct and significant negative effect on organizational performance and organizational commitment. The novelty of this research, Organizational commitment has a direct positive and significant effect on organizational performance